Teachers' Mixed Implementation of Mindset Mathematics Practices During and After a Novel Approach to Teacher Learning - Miriam Leshin; Tanya LaMar; Jo Boaler (MDPI AG, 2024)
Supporting teachers to transfer their learnings from innovative professional development settings to the classroom is challenging. In this paper, we investigate a novel approach to teacher learning, in which teachers from seven US districts taught in a mathematics summer camp using a research-based curriculum centered on student reasoning and mindset messages. We examined the practices teachers did and did not implement in their camp and school-year classrooms, as well as the possible reasons for the greater or lesser changes in practice. Through analysis of classroom video, teacher artifacts, and teacher interviews, we found that teachers implemented several important practices in both camp and school-year classrooms, namely posing open tasks, giving students ample time to collaborate, and asking questions that pushed students to reason. Interview analysis revealed that the act of centering students' reasoning and witnessing their subsequent engagement seemed to motivate teacher uptake of these practices. At the same time, however, teachers less frequently integrated mindset messaging directly into their teaching and gave space for the exploration of students' mistakes and struggles. These findings suggest implications for innovative professional development efforts outside of the school year, as well as incremental approaches.